Kinds of freshwater and their relation to ecosystem services and human well-being - Hayat, Shakeel; Gupta, Joyeeta (Water policy, 2016)
The concept of ecosystem services (ESS) has evolved as a link between society and the environment and is recognized by both natural and social scientists. While this concept is increasingly being developed and applied to various ecological systems, it has not been defined specifically for different kinds of water. As water circulation is crucial for large-scale services, such as climatic and hydrological regulation at global and regional scales, water provides specific ecological and anthropogenic services needed for a myriad of chemical, biological, and social needs. Various scholars mostly deal with one specific kind of water, while efforts at water governance need to understand that water passes through different phases and geographical locations providing different services at multiple scales within social-ecological systems. Hence, this paper addresses the question: what are the ESS of different kinds of freshwater and how are these services linked to human well-being? This paper investigates the literature on the subject to create a taxonomy of the kinds of water and their relations to ESS and human well-being. The paper concludes by identifying the implications for governing different kinds of water in order to enhance the potential for optimizing the ESS provided by water in its different phases.